Pengaruh Innovation Dan Job Crafting Yang Dimediasi Work Engagement Terhadap Employee Performance - fauzi, nadila; Ekhsan, Muhamad (Jurnal Manajerial, 2024)
Background – In the current era of globalization, manufacturing companies in the MM2100 Cikarang area are faced with increasingly fierce competition. To remain relevant and competitive, these companies need to continuously adapt and improve the performance of their employees. Aim – This study aims to determine the effect of innovation and work engagement on Work Engagement in manufacturing companies in the MM2100 Cikarang area. Design/ Methodology/ Approach – The data analysis technique used in this research method is SEM (Structural Equation Modeling) version 3.0 which is quantitative and includes data from 75 respondents who filled out the questionnaire. Findings – Innovation is able to contribute to employee performance innovation can improve efficiency, productivity, and quality of employee performance job crafting and work engagement have not been able to contribute to employee performance allegedly due to the mismatch between employee expectations and the reality of the work environment, innovation and job crafting are able to contribute to work engagement because employees can customize jobs according to individual preferences and skills, innovation and job crafting have not been able to contribute in mediating work engagement to employee performance possibly due to contextual factors. Conclusion - The construct model supports the significance of the hypotheses studied, while the indirect instrument has 1 insignificant relationship. Research Implication – Comparative research can also be conducted to analyze differences in findings among different manufacturing companies. Limitations – The object of research was only carried out on manufacturing companies in the MM2100 Cikarang area. So that the results of this study can only be generalized to similar companies in the region, not necessarily generalized to all manufacturing companies in Indonesia